Interval multivariate curve resolution in the dereplication of HPLC-DAD data from Jatropha gossypifolia - Pilon, Alan Cesar [UNESP]; Carneiro, R. L.; Carnevale Neto, F. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Castro-Gamboa, I. [UNESP] (Wiley, 2013)
Introduction Jatropha gossypifolia has been used quite extensively by traditional medicine for the treatment of several diseases in South America and Africa. This medicinal plant has therapeutic potential as a phytomedicine and therefore the establishment of innovative analytical methods to characterise their active components is crucial to the future development of a quality product. Objective To enhance the chromatographic resolution of HPLC-UV-diode-array detector (DAD) experiments applying chemometric tools. Methods Crude leave extracts from J. gossypifolia were analysed by HPLC-DAD. A chromatographic band deconvolution method was designed and applied using interval multivariate curve resolution by alternating least squares (MCR-ALS). Results The MCR-ALS method allowed the deconvolution from up to 117% more bands, compared with the original HPLC-DAD experiments, even in regions where the UV spectra showed high similarity. The method assisted in the dereplication of three C-glycosylflavones isomers: vitexin/isovitexin, orientin/homorientin and schaftoside/isoschaftoside. Conclusion The MCR-ALS method is shown to be a powerful tool to solve problems of chromatographic band overlapping from complex mixtures such as natural crude samples. Copyright © 2013 John Wiley & Sons, Ltd. Extracts from J. gossypifolia were analyzed by HPLC-DAD and, dereplicated applying MCR-ALS. The method assisted in the detection of three C-glycosylflavones isomers: vitexin/isovitexin, orientin/homorientin and schaftoside/isoschaftoside. The application of MCR-ALS allowed solving problems of chromatographic band overlapping from complex mixtures such as natural crude samples. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: C-glycosylflavones; Dereplication; HPLC-DAD; Jatropha gossypifolia; MCR-ALS; flavone derivative; homorientin; isoschaftoside; isovitexin; Jatropha gossypifolia extract; orientin; plant extract; schaftoside; unclassified drug; vitexin; drug determination; electrospray mass spectrometry; high performance liquid chromatography; high performance liquid chromatography ultraviolet diode array detector; Jatropha; nonhuman; plant leaf; tandem mass spectrometry; time of flight mass spectrometry; Jatropha gossypiifolia